Microwave-Assisted Hydrodistillation of Clove (Syzgium aromaticum) Stem Oil: Optimization and Chemical Constituents Analysis - Haqqyana Haqqyana; Ali Altway; Mahfud Mahfud (Universitas Gadjah Mada, 2021)
One of the extensively prosperous potential aromatic plants is the clove (Syzgium aromaticum). This is owing to all parts of this plant (bud, stem, and leaves) contain a decent amount of essential oils. The current study focuses on the use of microwave-assisted hydrodistillation (MHD) in extracting clove stem essential oils. This study aims to obtain the best possible combination of operating parameters for a high yield of clove stem oil using response surface methodology. The current study adopted a face-centered central composite design to optimize the MHD operational parameters, including the feed-to-solvent ratio, microwave power, and extraction time. The observed data from the experiments were fitted to a reduced quadratic polynomial equation. The three operational parameters were shown to significantly affect the extraction yield of the clove stem oil (p < 0.05), yet the statistical significance for the interaction between each parameter was considerably weak. Furthermore, the adjusted R2 value measured comparably to the corresponding R2 value with the difference below 0.2, implying a high correlation between experimental and model-predicted data. Thus, this result demonstrates the suitability of the model used in the experiment.